Evaluation of Students' Environmental Care Characters at Adiwiyata School (Case Study of SMPN 19 Palembang) - Dini Purwaningsih; Muhammad Faizal; Azizah Husin (Sriwijaya Journal of Environment, 2022)
Adiwiyata School program is unable directly build the student’s environmental care character. Therefore, it is necessary to evaluate the students’ environmental care character at schools that won the Adiwiyata Award. This study aims to evaluate the environmental care character of students at Adiwiyata School. This study used a mixed-method, which combines quantitative and qualitative descriptive methods. The research sample was taken using the purposive sampling technique where the researcher took 110 students as the research sample. There are 3 (three) indicators used to evaluate students' environmental care character. The first indicator is the environmental cleanliness concern which showed 89.88% of students gave a positive value response. The second indicator is the knowledge of waste management which showed 90.07% of students gave a positive score response, and the last indicator is the knowledge about reforestation and natural resource management which showed 82.62% of students gave a positive score response. Based on the three indicators used, the overall response was a positive value of 75%. In accordance, the results of the study show that the average value of positive responses was 88.08%. Thus, it can be said that the environmental care character of students at SMPN 19 Palembang is in the very good category.